Let's analyze the system of equations given in the problem:
From the linear combination method applied here, we have two equations stated after simplification:
- \( x + 2y = 15 \) (from \( 4(0.25x + 0.5y = 3.75) \))
- \( x - 2y = 3 \) (from \( \frac{1}{4}(4x - 8y = 12) \))
To find the solution for the system of equations, we can solve these two equations simultaneously.
-
Start with the first equation:
\[ x + 2y = 15 \quad (1) \]
-
Solve the second equation for \( x \):
\[ x - 2y = 3 \quad (2) \] Rearranging gives: \[ x = 2y + 3 \quad (3) \]
-
Substitute equation (3) into equation (1):
\[ (2y + 3) + 2y = 15 \]
Combining like terms:
\[ 4y + 3 = 15 \]
Subtracting 3 from both sides:
\[ 4y = 12 \]
Dividing both sides by 4:
\[ y = 3 \]
-
Substitute \( y = 3 \) back into equation (3) to find \( x \):
\[ x = 2(3) + 3 \] \[ x = 6 + 3 = 9 \]
Thus, the solution to the system of equations is:
\[ (x, y) = (9, 3) \]
Therefore, the correct answer from the options provided is:
(9, 3)